ENHANCED IONIC CONDUCTIVITY OF LAYERED-MNO2 ACCOMPANIED MORPHOLOGY EVOLUTION FOR AQUEOUS ZINC-ION BATTERY - Afiefudin, Mohamad; Setiawan, Asep Ridwan (Mesin, 2024)
Enhancing ionic conductivity is crucial for improving the performance of cathode materials in zinc-ion battery applications. In this study, nanoscale manipulation with nickel intercalation into the layered-MnO2 cathode structure was achieved through a hydrothermal reaction at 160°C for 10 hours. The results of Ni-layered-MnO2 synthesis showed a distinctive peak of layered-MnO2 cathode, as indicated by XRD results, and increased conductivity; its ionic conductivity was analyzed through electrochemical impedance spectroscopy (EIS), enabling rapid diffusion of Zn2+ ions and electron transfer. The distinctive morphology and structure of Ni-doped layered-MnO2 through scanning electron microscope (SEM) contribute to enhanced ionic conductivity and facilitate ion transportation, positioning it as a promising cathode material for aqueous zinc-ion battery applications.